Comparison of Outcomes of Endoscopic Fat Plug Myringoplasty and Chemical Cauterization for Closure of Small Central Tympanic Membrane Perforations (GAIMS Journal of Medical Sciences, 2024)
BackgroundVarious graft materials have been used for closure of small tympanic membrane perforations with varying success rates. This study was done to compare the success rates of endoscopic fat plug myringoplasty (EFPM) and chemical cauterization for managing small TM perforations.MethodologyThis was a prospective study conducted in ENT Department of a teaching hospital of western Gujarat from November 2020 to December 2022. 50 patients with small central dry perforation were randomly divided into 2 groups. 25 patients in Group A underwent endoscopic fat plug myringoplasty (EFPM) and 25 in Group B underwent trichloroacetic acid (TCA) application (chemical cauterization). At the end of 3 months (last follow-up) the perforation closure rates and hearing improvement were compared between the two groups.ResultsOut of 50 participants, 20 (40%) were males and 30 (60%) females. 36% participants belonged to 31-40 years of age group. The perforation closure with EFPM was significantly higher than chemical cauterization (92% vs 64%, p=0.0168) measured at 3 months follow-up. Similarly, the post operative hearing improvement was significantly better with EFPM that with chemical cauterization (p=0.0168).ConclusionsEFPM is an effective method for managing small central tympanic membrane perforations. It is a day-care procedure and success rate is equal or even better than other modalities of managing small TM perforations. This method should be used more often.